Impasses na aquisição de produtos da agricultura familiar para o Programa Nacional de Alimentação Escolar - Mattia, Vinícius (2024)
Clearly that it is necessary evaluating the efficiency of public policies in their implementation, due this, the aim of this thesis was to analyze the legal, productive, and organizational impasses affecting the expansion of purchase of products from family farmers to the Brazilian National School Lunch Program (NSLP). To realize the research and meet the proposed aim, four articles were developed. The first consisted of a literature review seeking to bring the main definitions, authors, and connections between the themes addressed in the thesis, as public policies, NSLP, family farming, social organizations, and sustainable development. The second article was based on a systematic review, where 17 articles were obtained through a search on the Scopus journal database, and a content analysis was conducted to highlight the main factors that hindered or contributed to family farmers' access to the NSLP. In the third article, a quantitative analysis of secondary data was performed, considering the transfer of funds from the National Fund for Education and the amount acquired from family farmers to the NSLP. This analysis covered 28 municipalities in three regions in the far west of Parana State between the years 2016 and 2019. Finally, in the fourth article, six of the municipalities highlighted in the previous article were selected based on their quantitative performances for explanatory research. This research involved the application of semi-structured interviews with key informants, focusing on identifying challenges in the acquisition of products from family farm to the NSLP, covering legal and documentary, productive, and organizational factors. As main results, it was possible to address the interconnection of relevant themes for the thesis, highlighting the relationship between public policies, the NSLP, family farming, social organizations, especially through associations and cooperatives, and sustainable development. Next, it analyzed the factors that influenced family farmers' access to the NSLP, emphasizing challenges such as unfamiliarity with legislation and lack of productive organization, and contributions such as the positive involvement of actors in the program and the presence of social organizations. The research also revealed quantitative disparities in the execution of the NSLP among municipalities, emphasizing the need for comprehensive analyses. When examining the operationalization of the NSLP in different locations, it identified key challenges in the acquisition of products from family farming, including legal and documentary factors, such as the need for greater participation of farmers and assistance technicians in the preparation of participation process and the responsibility of the NSLP sector for the elaboration of sales projects and organization of farmers' documentation. Productive factors included low diversity in production, lack of technical support, and low interest of farmers in organic/agroecological production, while organizational factors encompassed the lack of cooperative initiatives among stakeholders in the NSLP and a shortage of professionals, especially nutritionists, in the school alimentation sectors.